Ernst Toller y España - Pérez, Ana (Revista de Filología Alemana, 2010)
Like other exiled German intellectuals during the Nazi dictatorship (1933-1945), Ernst Toller strongly supported the cause of the Republic during the Spanish Civil War (1936- 1939). Toller was familiar with the situation in Spain from previous travels. As a result of his first journey to Spain (1931-1932) he published "Das neue Spanien" ("The new Spain"), a series of articles about the Spanish Republic in which the author explored different aspects of the political and social reality of the country, comparing it with the Weimar Republic. The last time he travelled to Spain (1938), the hunger and the misery of the civilian population encouraged him to initiate an international aid campaign. However, no sooner had he achieved his objective, than the Republic was defeated. Engulfed in a deep depression, Toller took his life in New York in May 1939.